(untitled) (Web of Teachers: Inderscience Research, 2025)
Analyzing an individual’s professional behavior and their career history, as well as the formation of initial professional goals, encompasses development leading up to professional life. The main objective of this creative approach is to select and guide young professionals, fostering skills to comprehend the essence of psychological cooperation and professional self-awareness concepts in this process. Practice is the criterion of truth. The validity of our knowledge is verified and confirmed through practice. The cognitive process is characterized by the transition from direct observation (sensory perception) to abstract thinking, and then to practical application.